A Large‐Scale Graphene–Bimetal Film Electrode with an Ultrahigh Mass Catalytic Activity for Durable Water Splitting. Issue 21 (2nd May 2018) - Yu, Xiaowen; Zhang, Miao; Tong, Yue; Li, Chun; Shi, Gaoquan
Abstract: The practical industralization of water splitting needs high‐efficient and cost‐effective catalytic electrodes. A versatile and scalable solution‐processing method to prepare such a catalytic electrode with high flexibility and conductivity is introduced. This preparation method is applicable for a wide variety of metal species and takes graphene sheets as metal carriers and film‐forming agents, resulting in 100% utilization of raw materials. The obtained graphene–bimetal film has excellent comprehensive performance with high areal activity and superior turnover frequency at a low mass loading of 0.05 mg cm −2, as well as a record‐high mass activity for oxygen or hydrogen evolution. The assembled two‐electrode configuration can be used in a practical full water splitting system, requiring a cell voltage of 1.58 or 1.50 V at 30 or 70 °C to afford a current density of 10 mA cm −2 ; it also exhibits a long‐term durability over 200 h, superior to most of the reported systems for the same purpose. This work provides a new platform for large‐scale and high‐yield production of electrocatalysts and also uncovers the design principles of catalytic electrodes with high mass activity toward industralization. Abstract : The graphene–bimetal film electrode with the record‐high mass catalytic activity for hydrogen or oxygen evolution is prepared via a versatile and industrializable solution‐processing method. The assembled two‐electrode configuration delivers a cell voltage of 1.58 V at 10 mA cm −2, as well as a long‐term durability over 200 h for full water splitting.